STUDI SIKAP TERHADAP PENDIDIKAN INKLUSI, IKLIM SEKOLAH DAN KEPUASAN KERJA GURU DI SEKOLAH INKLUSI - Nadya Astuti; Faridah Karyati; Alpha Ariani (Cangkal : Jurnal Ilmu Sosial Dan Humaniora, 2025)
Teacher job satisfaction is crucial because it motivates teachers to perform optimally, especially in inclusive schools, which are required to manage highly heterogeneous classes. Inclusive practices require the involvement of all aspects of the school, including teachers and the school climate. The purpose of this study was to obtain an overview of teachers' attitudes toward the implementation of inclusive education in schools, the school climate, and teacher job satisfaction. The research method was a survey using a questionnaire as a data collection tool administered to 25 teachers and interview. Data were processed using percentages. The results showed that almost half of the teachers had negative attitudes toward the implementation of inclusive education in schools. The school climate was classified as open with a low intimate dimension, and teacher job satisfaction was classified as moderate. Schools need to encourage various formal and informal activities related to the presence of children with special needs and inclusive education so that more teachers have positive attitudes toward the implementation of inclusive education, build better personal (intimate) relationships among teachers, and increase teacher job satisfaction.